2016
DOI: 10.1007/s00284-016-1125-6
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of the Staphylococcus aureus Inactivation Process Induced by a Multigas Plasma Jet

Abstract: To identify mechanisms underlying the bacterial inactivation process by atmospheric nonthermal plasma using a unique plasma jet that can generate various gas plasmas, Staphylococcus aureus were irradiated with carbon dioxide plasma, which produces a large amount of singlet oxygens, and nitrogen plasma, which produces a large amount of OH radicals. And damaged areas of plasma-treated bacteria were observed by field emission scanning electron microscopy, transmission electron microscopy, and atomic force microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Several dark granules were seen to be in combination with nucleic acid material. This combination could promote the accumulation of cell components within a short time, which would accelerate cell growth and multiplication ( Nilsson et al, 2002 ; Takamatsu et al, 2016 ). Moreover, fewer cells exhibit a gap between the cytoplasmic membrane and the cell wall.…”
Section: Resultsmentioning
confidence: 99%
“…Several dark granules were seen to be in combination with nucleic acid material. This combination could promote the accumulation of cell components within a short time, which would accelerate cell growth and multiplication ( Nilsson et al, 2002 ; Takamatsu et al, 2016 ). Moreover, fewer cells exhibit a gap between the cytoplasmic membrane and the cell wall.…”
Section: Resultsmentioning
confidence: 99%
“…The multi-gas plasma jet source [19][20][21][22] has a columnar like a pen and is connected to an AC power supply (Plasma Concept Tokyo, Inc., Tokyo, Japan) of 16 kHz and 9kV and a gas cylinder Plasma is The experiments were performed as follows. Blood with anticoagulants in a volume of 10 µL, was set on an adjustable platform and the multi-gas plasma jet was fixed at mm from the jet hole to sample.…”
Section: Plasma Sourcementioning
confidence: 99%
“…However, which one plays the most important role is still controversial, and it differs with the reactor type, gas type, etc. Recent studies have shown results that regard 1 O 2 as having the most important role in inactivating Staphylococcus aureus [ 13 , 15 ], bacteriophage T4 [ 16 ], yeast [ 12 ], and virus [ 14 ]. Such studies suggest that as long as researchers detect singlet oxygen, they will find that singlet oxygen plays the most important role.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, ROS and RNS are regarded as the primary causes of bacteria inactivation, which could attack bacteria and cause cell wall damage by electroporation and lipid oxidation, leading to DNA damage and protein modulation [ 11 ]. In recent years, more and more research has reported that •OH, 1 O 2 , •O 2 − , and ONOOH, but especially 1 O 2 , play important roles [ 12 , 13 , 14 , 15 , 16 ]. Our previous study using surface discharge plasma has also reported that •OH, 1 O 2 , and •O 2 − play important roles in inactivating A. spiroides and Escherichia coli [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%